STUDY OF CHROMOSOMAL ABNORMALITIES ENCOUNTERED IN A MATERNITY HOSPITAL BETWEEN 2010 AND 2014 - Cleiton Fantin; Marcelo Lasmar Santos; Lilian Barroso Carvalho; Natanael Martins Gomes; Larissa Nascimento Souza; Gabriela Bentes Sousa (Universidade Federal do Paraná, 2017)
This study sought to identify the existence of chromosomal abnormalities recorded in the medical records of live-born infants in a maternity hospital. This retrospective study analyzed the information contained in the medical records of the archives of the Medical Archiving Service of a maternity hospital in Amazonas state between January 2010 and December 2014, with the correlation between the chromosomal abnormalities and the characteristics of the mothers and the live-born infants also studied. A total of 15,621 records were analyzed, of these 163 presented congenital defects, with 15 diagnosed with chromosomal syndromes, divided into three types of anomalies: 13 individuals with Down syndrome, one with Patau syndrome and one with Dandy-Walker syndrome. This is the first registration of the occurrence and profile of births with chromosomal abnormalities in a maternity hospital. The result is of great importance for the public health service of the state. The performance of further studies may provide a better overview of the different genetic diseases of this state